Global organized crime : a reference handbook - Roth, Mitchel P., 1953- (Santa Barbara, Calif. : ABC-CLIO, 2010)
"ABC-CLIO's celebrated Contemporary World Issues series--available in both print and eBook formats--provides accurate, unbiased reference handbooks on the major topics of the day." "For details about all the titles in the Contemporary World Issues series, and information on how to buy them, visit www.abc-clio.com."--Jacket.
Global organized crime : a brief history -- Problems, controversies, and solutions -- Global organized crime groups -- Chronology -- Biographical sketches -- Data and documents -- Directory of organizations -- Resources.
Includes bibliographical references and index.
Keywords: Organized crime -- Handbooks, manuals, etc; Transnational crime -- Handbooks, manuals, etc; Organized crime; Transnational crime; Handbooks and manuals; Reference works; Reference works; Nonfiction